NAPLAN data: a new policy assemblage and mode of governance in Australian schooling. (1st November 2016) - Gable, Alison; Lingard, Bob
ABSTRACT: As part of a policy assemblage, the National Assessment Program – Literacy and Numeracy (NAPLAN) is representative of a new mode of governance for Australia's schooling systems, indicative of international trends in educational accountability based on testing. The policy assumption was that the introduction of a national performance measurement system would tightly couple school practices to national agendas targeted at improving learning outcomes. This paper presents a comparative case study of two primary schools within a single Queensland region to interrogate how coupling and decoupling strategies are enacted in respect of the policy usage of NAPLAN data. The granular analysis of the governance relationship between the school principals and their supervisors is set against the politics, policies and pressures of NAPLAN that recast the initiative as high stakes for systems, schools and their leadership. Specifically, we argue that Queensland's choice and enactment of policy instruments have produced a new mode of governance of principal conduct, but one mediated by the specific contexts of the two schools. The analysis shows how this mode has precipitated two types of decoupling.